Pengaruh Corporate Governance dan Sales Growth terhadap Tax Avoidance di Bursa Efek Indonesia (BEI) 2014-2018 - Desy Fitri Astuti; Riana Rahmawati Dewi; Rosa Nikmatul Fajri (Universitas Batanghari Jambi, 2020)
Tax Avoidance is an effort to minimize the tax burden that is still in the realm of tax law. The purpose of the study was to analyze corporate governance and sales growth on tax avoidance. The research population is 70 basic and chemical industry companies listed on the Indonesia Stock Exchange in 2014-2018. Sampling using a purposive sampling technique, 7 companies were selected. The data analysis technique used is multiple linear regression. The results of this study are Institutional Ownership, Majerial Ownership, the number of boards of Commissioners and Sales growth simultaneously influence Tax Avoidance. Partially Institutional Ownership and the number of the Board of Commissioners influences Tax Avoidance. While Sales growth has no effect on Tax Avoidance. the benefits of this research are being able to broaden insight and at the same time gain knowledge about the effect of corporate governance and sales growth on tax avoidance.